Exploring a possibility to control the stressedstrained state of cylinder liners in diesel engines by the tribotechnology of alignment - Aulin, Viktor; Hrynkiv, Andrii; Lysenko, Sergii; Dykha, Aleksandr; Zamota, Taras; Dzyura, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2019)
Our research into the formation of a functional copper-containing surface layer on parts of automobile engines by using an alignment tribotechnology has established a decrease in the wear of parts during their operation. It was found that the formed coating creates an elastic layer that reduces strains in a material of engine parts. Our experimental study of the coercive force of parts’ working surfaces has confirmed a decrease in the accumulation of destructive stresses in the near-surface layers of a components’ material. In turn, a comparative analysis of the obtained results by using a coercimetric method confirms that the proposed aligning tribotechnology leads to reduction of the stressed-strained state and makes it possible to improve wear resistance and enhance the technical condition of diesel engine cylinder liners: the magnitude of coercive force reduces by 7.5 %, while operating time increases by 16 %. In this case, at larger operating time: 254.8 thousand km against 220.5 thousand km, according to data on the coercive force (14.2…9.1) A/cm and (13.2…9.0) А/cm, it is almost in the same condition. The functional surface layer forms when introducing a composite oil to the tribotechnology of cold alignment of an automobile powertrain. We have proposed and implemented a circuit to connect electric current to components at an engine’s cylinder-piston group as a result of studying the developed tribotechnology of alignment. The features of this scheme are that the constant electric current is supplied by the plus polarity, through the brush-collector node, to the crankshaft, and by the minus polarity, through the clamping contact, to the crankcase block. The research results suggest a possibility to control the internal strains and the subsequent magnitude of wear in a material of working heavily-loaded components of automobile powertrains provided they are serviced properly. The proposed tribotechnology of alignment could be of interest for both service departments at trucking companies and for car service stations.